The influence of structural organization of epilithic and endolithic lichens on limestone weathering - Morando, M; Wilhelm, K; Matteucci, E; Martire, L; Piervittori, R; Viles, H; Favero-Longo, S (Wiley, 2017)
Hyphal penetration, mineral dissolution and neoformation at the lichen–rock interface have been widely characterized by microscopic and spectroscopic studies, and considered as proxies of lichen deterioration of stone substrates. However, these phenomena have not been clearly related to experimental data on physical properties related to stone durability, and the physical consequences of lichen removal from stone surfaces have also been overlooked. In this study, we combine microscopic and spectroscopic characterization of the structural organization of epi- and endolithic lichens (Caloplaca marina (Wedd.) Du Rietz, Caloplaca ochracea (Schaer.) Flagey, Bagliettoa baldensis (A.Massal.) Vězda, Porina linearis (Leight.) Zahlbr., Verrucaria nigrescens Pers.) at the interface with limestones of interest for Cultural Heritage (Portland Limestone, Botticino Limestone), with analysis of rock properties (water absorption, surface hardness) relevant for durability, before and after the removal or scraping of lichen thalli. Observations using reflected-light and electron microscopy, and Raman analyses, showed lichen–limestone stratified interfaces, differing in the presence/absence and depth of lichen anatomical layers (lithocortex, photobiont layer, pervasive and sparse hyphal penetration component) depending on species and lithology. Specific structural organizations of lichen–rock interface were found to be associated with differential patterns of water absorption increase, evaluated by Karsten tube, in comparison with surfaces with microbial biofilms only, even more pronounced after the removal or scraping of the upper structural layers. Equotip measurements on surfaces bearing intact thalli showed lower hardness in comparison with control surfaces. By contrast, after the removal or scraping procedures, Equotip values were similar to or higher than those of controls, suggesting that the increasing open porosity may be related to a biogenic hardening process. Such counterposed patterns of porosity increase and hardening need to be considered when models relating lichen occurrence on limestones and biogeomorphological surface evolution are proposed, and to evaluate the consequences of lichen removal from stone-built cultural heritage.